Anionic liposomes prepared without organic solvents for effective siRNA delivery - Xiu Han; Yan Lu; Zhaoluo Xu; Yanan Chu; Xueping Ma; Haiping Wu; Bingjie Zou; Guohua Zhou (IET Nanobiotechnology)
Abstract Currently, organic solvents are necessary for the preparation of anionic liposomes for siRNA delivery. The removal of organic solvent is time‐consuming and the residual organic solvent is not only a hidden danger, but also affects the stability of anionic liposomes. Glycerol, which is physiologically compatible and does not need to be removed, is used to promote the dispersion of lipids and the formation of anionic liposomes. Additionally, the preparation process is simple and not time‐consuming. The results showed that anionic liposomes, which were typically spherical with a particle size of 188.9 nm were successfully prepared with glycerol. And with the help of Ca2+, siRNA was encapsulated in anionic liposomes. The highest encapsulation efficiency at 2.4 mM Ca2+ reached 91%. And the formation of calcium phosphate could promote the endosomal escape of siRNA effectively. The results from cell viability showed that the anionic liposomes had no obvious cytotoxicity. It was also verified that anionic liposomes could improve the resistance of siRNA against degradation. Additionally, siRNA delivered by anionic liposomes could play an effective role in knockout. Therefore, anionic liposomes prepared with glycerol will be a safe and effective delivery platform for siRNA and even other nucleic acid drugs.